2021
DOI: 10.3389/fpubh.2021.733458
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emotional Labor on Presenteeism of Chinese Nurses in Tertiary-Level Hospitals: The Mediating Role of Job Burnout

Abstract: Background: Employees who are physically present but work insufficiently because of illness are deemed as having presenteeism. In the health care setting, the issue has taken on greater importance because of the impairment of the physical and mental health of nurses and the nursing safety of the patients. According to the Job Demand-Resource Model, burnout may link emotional labor with presenteeism. Thus, this study analyzed the role of burnout as a mediating factor between the three types of emotional labor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In particular, item 10 (“I work at developing the feeling inside of me that I need to show to customers”) showed the highest score. Most nurses agreed they overcame negative emotions at work, got along with others in a friendly way, and used deep acting emotional labor strategies, which means to keep inner feelings consistent with their displayed expression, instead of fake acting at work [ 49 ]. They may excel at actively regulating internal emotions and actively change to promote self-action, resulting in behavior consistent with organizational expectations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, item 10 (“I work at developing the feeling inside of me that I need to show to customers”) showed the highest score. Most nurses agreed they overcame negative emotions at work, got along with others in a friendly way, and used deep acting emotional labor strategies, which means to keep inner feelings consistent with their displayed expression, instead of fake acting at work [ 49 ]. They may excel at actively regulating internal emotions and actively change to promote self-action, resulting in behavior consistent with organizational expectations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we replaced ‘customers’ with ‘patients’. The Chinese Emotional Labour Scale is widely used by people from all walks of life and has high reliability and validity 26 27. In this study, Cronbach’s alpha coefficients for the SA, DA and NA subscales were 0.88, 0.79 and 0.89, respectively.…”
Section: Methodsmentioning
confidence: 66%
“…Although occupational stress and anxiety cannot cause occupational diseases by speci c factors such as physical and chemical, there are non-speci c ways of damage to the body, such as increased absenteeism, reduced work capacity, and unexpected medical incidents [36,37] .The median and 25th and 75th percentile job competency scores of Xinjiang biosafety laboratory staff in this study were 39.0 (36.0, 42.0) points. The general characteristics and occupational characteristics were set as confounders by propensity score matching, and the results after eliminating the confounders showed that there was an effect of anxiety and occupational stress on work ability, and the prevalence of poor work ability in the anxiety group was more than twice as high as that in the no-anxiety group.…”
Section: Dicussionmentioning
confidence: 78%